RESOLUTION OF LAND DISPUTES IN URBAN AREAS THROUGH AN AGRARIAN LAW APPROACH AND THE IMPLEMENTATION OF AGRARIAN REFORM POLICIES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyse the process and implementation of land dispute resolution in urban areas of Indonesia, with a focus on legal aspects and agrarian reform policies. The main issues raised include the high rate of land conflicts, the resolution process through litigation and non-litigation channels, and the administrative and social obstacles encountered in practice. This study uses a juridical-empirical approach with case study and literature review methods, as well as taking into account relevant laws and regulations. The results show that dispute resolution through mediation and conciliation at the land office is an effective solution, but still faces obstacles in terms of public understanding and limited administrative data. Comprehensive implementation of agrarian reform policies is believed to be capable of reducing land conflicts in urban areas if supported by inter-institutional synergy and community empowerment. This study concludes that the success of land dispute resolution depends not only on the accuracy of regulations, but also on social aspects, public education, and improving the quality of implementing officials.